2010
DOI: 10.1007/s10096-010-1087-8
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of ST121 in community-associated methicillin-susceptible Staphylococcus aureus lineages responsible for skin and soft tissue infections in Portuguese children

Abstract: In order to evaluate the incidence of communityassociated methicillin-resistant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 38 publications
2
25
2
Order By: Relevance
“…27 Moreover, the lineage t2155-ST121-CC121 found in one of our MSSA strains, has also been detected among MRSA implicated in skin and soft tissues infections. 32 Interestingly, this strain was isolated from a skin lesion of an individual who worked sporadically in the farm (Case 6). In the same line, many studies have associated the MRSA-ST22 genetic lineage with frequent infections in Europe.…”
Section: Discussionmentioning
confidence: 98%
“…27 Moreover, the lineage t2155-ST121-CC121 found in one of our MSSA strains, has also been detected among MRSA implicated in skin and soft tissues infections. 32 Interestingly, this strain was isolated from a skin lesion of an individual who worked sporadically in the farm (Case 6). In the same line, many studies have associated the MRSA-ST22 genetic lineage with frequent infections in Europe.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, probably the prevalence of MSSA is also dependent on the type of infection analyzed, since in another study performed in Portugal it was shown that the most prevalent clone in skin and soft tissue infections was ST121. 12 This clonal type was neither observed in the 2006 or 2011 surveys in Portugal in which bacteremia isolates were recovered and analyzed. 22 Another evidence for the dynamic nature of MSSA population is the finding in our study of four spa types that were common between MSSA and MRSA, associated to ST5, ST8, and ST22.…”
Section: Dynamics Of Mssa Population and Its Relatedness To Mrsamentioning
confidence: 97%
“…Moreover, this clone had been also reported in China, Nigeria and Germany Conceição et al, 2011;Schefold et al, 2007). It is noteworthy that two PVL -positive ST 121-SCCmec V-MRSA isolates emerged in Cambodia (Chheng et al, 2009).…”
Section: Mlst-ccmentioning
confidence: 62%
“…The ST121 was one of the predominant lineages of PVL-positive MSSA in the world (Rasigade et al, 2010) and the dominant clone in MSSA throughout Russia and Portugal (Vorobieva et al, 2008;Conceição et al, 2011). Moreover, this clone had been also reported in China, Nigeria and Germany Conceição et al, 2011;Schefold et al, 2007).…”
Section: Mlst-ccmentioning
confidence: 87%